Seismic response characteristics of polymer anti-seepage wall in earth dam based on earthquake wave motion input method. (January 2023) - Wang, Fuming; Tulamaiti, Yunusijiang; Fang, Hongyuan; Yu, Xiang; Zhou, Chenguang
Abstract: The polymer anti-seepage wall has great application value in the reinforcement of earth dams. At present, the research on polymer anti-seepage walls is limited to the analysis of material properties and mechanical properties under static conditions. The application of polymer anti-seepage walls in earth dams in earthquake area is limited due to lack of research on seismic performance under strong earthquake. Therefore, in this paper, the earthquake wave motion input method is adopted to systematically study the seismic response characteristics of the polymer anti-seepage wall in earth dam. The research shows that the properties of polymer materials and the spectral content of the input ground motion have different effects on the acceleration response of the anti-seepage wall; After the earthquake wave motion input method is adopted, the reduction rates of the horizontal and vertical acceleration of the polymer anti-seepage wall relative to the traditional uniform excitation method range from 10.37% to 34.19% and 12.13% to 36.50%, respectively; For the dam project studied in this paper, the 25° incident angle of the SV wave and the 60° incident angle of the P wave are the most unfavorable incident angles; Compared with concrete anti-seepage walls, polymer anti-seepage walls have better dynamic coordination performance;